Awakening Philippine Cultural Consciousness in the Youth through Amelia Lapeña-Bonifacio’s Papet Pasyon - Ramolete, Amihan Bonifacio; Tiatco, Sir Anril Pineda (Harmonia: Journal of Arts Research and Education, 2024)
This article aims to explore how the staging of Papet Pasyon, a children’s play by Amelia Lapeña-Bonifacio, a Philippine National Artist, impart and continues to communicate to the local younger audience an understanding of culture and an appreciation of the art of puppetry. This is then followed by the conceptualization of the actual staging of the play vis-à-vis her vision of a children’s theatre. Afterward, Papet Pasyon is asserted as a pedagogy for younger audiences. Results of the study show (1) how the pre-show conversation prepares the audience for the performance and how it provides an understanding of Filipino cultural traditions and an appreciation of the art of puppetry; (2) how the performance serves as a venue for experiential learning; (3) how the art of puppetry challenges one’s imagination in manipulating the puppet (in the case of the puppeteer) and in creating meanings from what they hear and see onstage (in the case of the audience); (4) cooperation and integration are made evident by the interactions between the puppet and the puppeteer and the puppet and puppeteer with the audience; and (5) that although puppetry is foreign to the audience, they have expressed appreciation of the art form by repeatedly watching the performance through the years.